PEMANFAATAN MEDIA SOSIAL WHATS’APP GROUP SEBAGAI WADAH PENYAMPAIAN INFORMASI DAN KOMUNIKASI OLEH KELURAHAN MATSUM I - Ardi Septiadi; Muhammad Alfikri (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
The more developed a civilization, the more developed the technology used. Likewise in communication media, where conventional media develops so as to create New Media (new media). New media is a communication medium that utilizes the internet network and is operated through computer or digital technology. New media are rapidly developing and progressing rapidly so that they can form virtual public spaces, one of which is Social Media. The purpose of this research is to find out how the use of Whats'app Group social media as a forum for delivering information and communication by the Matsum I village. From this analysis using qualitative research methods with a descriptive approach. The primary data source in this analysis is in-depth interviews and uses secondary data sources from the theoretical perspective of books and journals. Data collection techniques were collected from the results of observations, documentation and interviews with the Matsum I village. The validity of the data was combined with data collection techniques and analyzed and seen for validity. The results showed that with the existence of a group on whats'app social media among the Matsum I village, the process of interaction, services and information that was shared was easier and very effective from the kelurahan, the head of the neighborhood and the local community. This makes it easier for each individual to convey and get information quickly even in a matter of seconds. By utilizing social media Whats'app group information is easily obtained without being constrained by distance and time.